Exercise, Processing Speed, and Subsequent Falls: A Secondary Analysis of a 12-Month Randomized Controlled Trial. (9th November 2020) - Liu-Ambrose, Teresa; Davis, Jennifer C; Falck, Ryan S; Best, John R; Dao, Elizabeth; Vesely, Kristin; Ghag, Cheyenne; Rosano, Caterina; Hsu, C L; Dian, Larry; Cook, Wendy; Madden, Kenneth M; et al.
Abstract: Background: Strength and balance retraining exercises reduce the rate of subsequent falls in community-dwelling older adults who have previously fallen. Exercise can also improve cognitive function, including processing speed. Given processing speed predicts subsequent falls, we aimed to determine whether improved processing speed mediated the effects of the Otago Exercise Program on the rate of subsequent: (i) total falls, (ii) non-injurious falls, (iii) moderate injurious falls, and (iv) serious injurious falls. Method: A secondary complete case analysis of a 12-month, single-blind, randomized clinical trial among 256 of 344 adults aged at least 70 years who fell in the previous 12 months. Participants were randomized 1:1 to receive usual care plus the Otago Exercise Program ( n = 123) or usual care ( n = 133), consisting of fall prevention care provided by a geriatrician. The primary outcome was self-reported number of falls over 12 months (ie, rate of falls). Processing speed was assessed at baseline and at 12 months by the Digit Symbol Substitution Test (DSST). Causal mediation analyses were conducted using quasi-Bayesian estimates and 95% confidence intervals. Results: Exercise significantly reduced the rate of subsequent moderate injurious falls (IRR = 0.49; 95% CI: 0.31, 0.77; p = .002) and improved processing speed (estimated mean difference: 1.16 points; 95% CI: 0.11, 2.21). Improved DSST mediated the effect of exercise on the rate of subsequent moderate injurious falls (estimate: −0.06; 95% CI: −0.15, −0.001; p = .036). Conclusion: Improved processing speed may be a mechanism by which exercise reduces subsequent moderate injurious falls in older adults who fell previously. Clinical Trials Registration Number: ClinicalTrials.gov Protocol Registration System: NCT01029171: https://clinicaltrials.gov/ct2/show/NCT01029171 NCT00323596: https://clinicaltrials.gov/ct2/show/NCT00323596